Optimasi Induksi Tunas Aksiler Dendrobium nobile Melalui Kombinasi 2-iP dan 2,4-D In Vitro - Sofiatul Milah; Lili Sugiyarto; Ratnawati; Suyitno Aloysius; Ixora Sartika Mercuriani (Program Studi Agroteknologi INSTIPER, 2023)
This research aims to determine optimum combination of addition 2-iP and 2,4-D with different concentration and the nodus position for induction Dendrobium Red Emperor ‘Prince’ axial shoots. The research employed a CFR design with two factors, namely: variation of combined concentration 2-iP and 2,4-D (A: 1 ppm 2-iP + 2 ppm 2,4-D; B: 2 ppm 2-iP + 1,5 ppm 2,4-D; C: 3 ppm 2-iP + 1 ppm 2,4-D; D: 4 ppm 2-iP + 0,5 ppm 2,4-D) each treatment was repeated 6 times and the nodal position (top, middle, bottom). The basic medium is NP+CW. The axillary bud growth is measured based on the time of bud emerge, shoot growth, explant percentage which form axillary bud, root growth, and plantlet wet weight. Data obtained were analyzed using ANOVA and continued with DMRT 5%. Results show that B treatment give fastest bud emerging time, and highest stem diameter, buds height, leaves length, leaves width, roots length. A treatment shows best results on shoots number, plantlet wet weight, number of leaves, and number of roots. The optimum combined concentration of 2-iP and 2,4-D to induce axillary shoots is 2 ppm 2-iP + 1,5 ppm 2,4-D, whilst best nodus position is the top one.